Analysis of the Implementation of Inactive Archive Maintenance at PT XYZ - Dewi Kurnia Putri; Marsofiyati Marsofiyati; Maulana Amirul Adha (Pusat Riset dan Inovasi Nasional, 2025)
This study seeks to examine the implementation, challenges, and improvement efforts concerning inactive records maintenance at PT XYZ Head Office, Cawang, East Jakarta. The research adopts a descriptive qualitative method using a case study approach. Data collection techniques include observation, interviews, and documentation. The research informants were selected using purposive sampling, consisting of employees directly involved in inactive records management within the Secretary and General Affairs units. The findings reveal that the implementation of inactive records maintenance at PT XYZ has been carried out through several efforts, including environmental control of the records storage area, records security, and the arrangement and storage of inactive records in accordance with applicable regulations. However, the implementation has not been fully effective due to several constraints, including limited storage facilities and infrastructure, particularly filing cabinets, as well as limited human resources with sufficient competencies in records management. These conditions have resulted in the accumulation of records boxes and increased risks of damage and loss of inactive records. The efforts undertaken by PT XYZ to address these obstacles include organizing records based on the Records Retention Schedule (RRS), implementing security systems in the records storage area, and planning improvements in storage facilities as well as enhancing employee competencies through records management training. This study is expected to provide contributions, insights, and serve as an evaluation and recommendation for the company to improve the effectiveness of implementation of inactive records maintenance.